Miss Marple's Final Cases - Christie, Agatha 1890-1976 (London HarperCollins Publisher, 1994)
Six gripping cases with one thing in common - the astonishing deductive powers of Jane Marple.
Originally published: London : Collins, 1979.
Keywords: Crime -- Women Detectives -- Older Woman